Designing the structure and architecture of situation-aware security information systems for residential complexes - Kunanets, Nataliia; Zhovnir, Yuriy; Burov, Yevhen; Duda, Oleksii; Pasichnyk, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2025)
Security information systems constitute a significant application domain for the concept of situational awareness. The object of this study is security information systems for residential complexes. The task addressed involved devsigning an efficient, flexible, and adaptive structure to ensure situational awareness in security information systems. Unlike existing systems, this structure is based on the integration of intelligent agents, server services, and a central unit that interacts with the Internet of Things (IoT) network. The proposed system ensures the autonomy of intelligent agents, which perform specialized tasks using integrated intelligent sensors, while server services handle basic computational tasks such as machine learning, pattern matching, and model construction. The central unit aggregates information, implements reasoning procedures, and identifies situations for the entire system. An architecture has been proposed that includes three main subsystems: video surveillance, access control, and operator service management. The essence of the results is the development of a flexible architecture that effectively combines IoT technologies with the situational awareness approach. The research results were achieved by integrating innovative approaches such as the use of intelligent agents, machine learning, and situational analysis, enabling a flexible distribution of functions among system components depending on the specific task requirements. The distinctive features of this architecture facilitate the implementation of the situational awareness principle and support continuous system learning processes. Given its modular architecture, the proposed system could be applied in extensive residential networks serviced by Internet providers, as well as in associations of co-owners of multi-apartment buildings. The formalization of architectural elements simplifies the process of designing and deploying systems, making them accessible for a wide range of applications in residential complexes by Internet service providers